Less Invasive Modified Extradural Temporopolar Approach for Paraclinoid Lesions: Operative Technique and Surgical Results in 80 Consecutive Patients - Otani, Naoki (J Neurol Surg B Skull Base, 2018)
Background  Extradural temporopolar approach for paraclinoid lesions can provide extensive and early exposure of the anterior clinoid process, and complete mobilization and decompression of the optic nerve and internal carotid artery, which can prevent intraoperative neurovascular injury. The present study investigated the usefulness of our less invasive modified technique and discussed its operative nuances. Methods  We retrospectively reviewed medical charts of 80 consecutive patients with neoplastic (21 patients) and vascular lesions (59 patients) who underwent the modified extradural temporopolar approach between September 2009 and March 2014. Results  Preoperative visual acuity worsened in 4 patients (5.0%) and worsening of visual field function occurred in 10 patients (12.5%). Postoperative outcome was good recovery in 71 patients, moderate disability in 6, severe disability in 2, and death in 1 (due to reruptured aneurysm). No operation-related mortality occurred in the series. Conclusion  Less invasive modified extradural temporopolar approach is safe and can be recommended for the surgical treatment of deeply located aneurysms and skull base tumors to reduce the risk of intraoperative optic neurovascular injury.